Die Heringsfischerei an der Ostküste Kanadas - Schumacher, A. (1962)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010